Pemberdayaan Ekonomi Lokal Melalui Sosialisasi Teknik Budidaya Dan Pembesaran Ikan Nila Salin Yang Efisien - Hamdan Arif Fatoni; Faisal Adit Prasetyo; Rohmad Hidayatullah; Sugeng Wahyudi; Muhammad Ali Mahmudi; Uyunul Jazilah (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2026)
The KP2M program in Penanjan Village, Paciran Subdistrict, Lamongan, focused on community empowerment through brackish water tilapia (nila salin) cultivation. This commodity was chosen for its high economic value, adaptability to brackish water, and as a solution to limited land and freshwater resources. The main problems faced by the community were limited technical knowledge and inefficient pond utilization. Activities included socialization, training, and hands-on practice in seed selection, feed management, water quality, and pest control. As a result, community knowledge and skills improved, along with awareness of tilapia as a sustainable business. Despite water fluctuation challenges, continuous mentoring is expected to increase income and community independence.